2020
DOI: 10.1007/s40487-020-00126-0
|View full text |Cite
|
Sign up to set email alerts
|

Response to Abemaciclib After 10 Lines of Therapy Including Palbociclib in Metastatic Breast Cancer: A Case Report With Literature Review

Abstract: Metastatic breast cancer (BC) is considered incurable, and it is generally treated with sequential single-agent therapies to control it with palliative intent. Cyclin-dependent kinase 4/6 inhibitors (CDK4/6i) are used in the frontline setting of hormone receptor (HR)-positive, HER2-negative BC, and guidelines discourage the use of a second-line CDK4/6i after failure of first-line use of this class of drugs due to lack of data supporting this practice. We report a case of a postmenopausal woman with HR-positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…It is an anti-cancerous agent that is reported to dually inhibit cyclin-dependent kinase 4 and 6 (CDK 4 and CDK 6). Abemaciclib is an FDA-approved drug used for the treatment of HR-positive and HER-negative metastatic breast cancer in combination with Fulvestrant [41]. Further, the drug has been used in various other trials including for the treatment of melanoma, lymphoma and solid tumors [42,43].…”
Section: Scaffold Analysismentioning
confidence: 99%
“…It is an anti-cancerous agent that is reported to dually inhibit cyclin-dependent kinase 4 and 6 (CDK 4 and CDK 6). Abemaciclib is an FDA-approved drug used for the treatment of HR-positive and HER-negative metastatic breast cancer in combination with Fulvestrant [41]. Further, the drug has been used in various other trials including for the treatment of melanoma, lymphoma and solid tumors [42,43].…”
Section: Scaffold Analysismentioning
confidence: 99%
“…Another case series published by Mariotti V. et al demonstrated a response with abemaciclib in some patients after progression on palbociclib with a median PFS of 7.0 months (range 1.8-12.1) [32]. Some other case reports and single-center experiences also suggest the clinical efficacy of abemaciclib in this setting [33][34][35].…”
Section: Discussionmentioning
confidence: 99%